ПИТАННЯ РЕАЛІЗАЦІЇ КОМПЕТЕНТНІСНОГО ПІДХОДУ У ВИЩИЙ ПРОФЕСІЙНІЙ ОСВІТІ (Педагогіка вищої та середньої школи, 2008)
This article considers the problem of realization of the Competential Approach in the higher professional school. It reveals the main points of view on its introduction and problems concerning it; its aims, main constituents, principals and results are analyzed.